MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI BERMAIN DENGAN BARANG BEKAS - Sabaria Agustina; M. Nasirun; Delrefi D. (Jurnal Ilmiah POTENSIA, 2018)
The problem in this research is the low of fine motor skills of child. This classroom action research aims to improve the fine motor of children through playing activities with the media used plastic bottles and cartons of former group B PAUD Aulia Bengkulu City. Whether through the activities of playing with used media used plastic bottles and used cardboard can improve the 3 aspects of tightening, holding, and coordinating the eyes and hands. Subjects in this study were the children of group B who held 10 children consisting of 6 girls, and 4 boys. This classroom action research is conducted in 2 cycles and each cycle consists of three meetings. Technique is observation, with data analysis technique use average. The result of this study is proven by the fine motor skills of children can be improved through playing activity with the media used plastic bottles and used cardboard, with learning mastery of 88% average total motor fine result of children 4.4 (good). From the results of the research that produces, it is advisable for teachers to apply play activities with the media used plastic bottles and used cardboard, and for further research is expected to research about fine motor skills through play activities with other aspects.